Possible involvement of the RARRES2/CMKLR1-system in metabolic and reproductive parameters in Holstein dairy cows - Namya Mellouk; Christelle Ramé; Mélodie Diot; Eric Briant; Jean-Luc Touzé; Daniel Guillaume; Pascal Froment; Joëlle Dupont (BMC, 2019)
Abstract Background In dairy cows, the energy cost of milk yield results in a negative energy balance (EB) and body fat mobilization that impairs reproductive efficiency. Emerging evidence suggests that the novel adipokines, Retinoic acid receptor responder protein 2 (RARRES2), and its main receptor, Chemokine-like receptor 1 (CMKLR1) are involved in the regulation of metabolic and ovarian functions. So, we investigated in a first experiment the plasma RARRES2, and RARRES2 and CMKLR1 mRNA expression levels in subcutaneous adipose tissue (SAT) and granulosa cells (GC) at different times of body fat mobilization in dairy cows (4, 8, 20 and 44 weeks postpartum, wk. pp. for SAT and 8, 20 and 44 wk. pp. for GC). Then, in a second experiment we examined the effect of high (HE) and low energy (LE) diets on the RARRES2 system and its links with metabolic and reproductive parameters. Methods The first experiment included 9 animals fed with HE diet from 4 to 44 wk. pp. and the second one included animals fed either a HE diet (n = 8) or a LE diet (n = 8) from − 4 to 16 wk. peripartum. In both experiments, various metabolic and reproductive parameters were determined and associated with plasma RARRES2 as measured by bovine ELISA. RARRES2 and CMKLR1 mRNA expression levels were analyzed by RT-qPCR in SAT after biopsy and GC after aspiration of follicles. Results Plasma RARRES2 levels were higher at 4 wk. pp. as compared to 20 and 44 wk. pp. and they were positively correlated with body fat mobilization and milk yield. RARRES2 and CMKLR1 mRNA expression levels increased from 4 to 8 wk. pp. (fat mobilization, EB < 0) and remained unchanged at 20 and 44 wk. pp. (fat reconstitution, EB > 0) as compared to 4 wk. pp. in SAT. RARRES2 and CMKLR1 mRNA levels decreased from 8 to 44 wk. pp. in GC from small follicles. In the second experiment, plasma RARRES2 increased from − 4 to 8 wk. peripartum similarly in both LE and HE cows. In addition, the area under of plasma RARRES2 curve was highly negatively associated with the number of small follicles obtained in HE animals during the cycle before the first artificial insemination. In SAT of HE cows, RARRES2 mRNA expression decreased at 1 wk. pp. compared to − 4 and 16 wk. peripartum whereas opposite expression patterns were obtained for CMKLR1. Similar results were observed for CMKLR1 mRNA expression in LE cows while there was no variation in RARRES2 mRNA expression. Moreover, RARRES2 mRNA was higher expressed in LE than in HE cows at 1 wk. pp. Conclusions The lactation-induced fat and energy mobilization influenced plasma RARRES2 profile and mRNA expression pattern of RARRES2 and CMKLR1 similarly in both SAT and GC. In addition, the energy content of the diet did not affect plasma RARRES2 but it altered RARRES2 mRNA expression in SAT and the area under the curve of plasma RARRES2 that was negatively associated to the number of small follicles in HE animals. Thus, RARRES2 could be a metabolic or ovarian signal involved in the interactions between metabolic and reproductive functions in dairy cows.